Peningkatan sintasan dan pertumbuhan benih ikan tengadak, Barbonymus schwanenfeldii (Bleeker, 1854) melalui pengaturan suhu dan magnesium - Novi Susianti; Kukuh Nirmala; Ani Widiyati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
This study aimed to determine the optimal temperature and magnesium levels in rearing media to increase the growth of tinfoil barb larvae (Barbonymus schwanenfeldii). The experimental design was arranged in factorial completely randomized design with three replications. The treatment included three temperature viz. 26°C, 28°C, dan 30°C and four additional magnesium viz. 0, 10, 20, 30 mg L-1. Fish stocking density was 1 ind. L-1 with an average length of 2.00±0.03 cm and an average initial weight of 0.33±0.01 g. The result showed that the combination of temperature 28°C with addition magnesium 20 mg L-1 was the best rearing media to increase the growth of tinfoil barb larvae ie. the daily average growth rate was 8.93±0.23% and growth of absolute length was 1.78±0.02 cm. The highest of survival rate (95.24%) also achieved in the treatment of temperature 28°C. Abstrak Penelitian ini bertujuan untuk menentukan suhu dan magnesium yang optimal pada pemeliharaan benih ikan tengadak (Barbonymus schwanenfeldii) agar dapat meningkatkan sintasan dan pertumbuhan. Rancangan percobaan yang diguna-kan adalah rancangan acak lengkap (RAL) faktorial dengan tiga ulangan. Perlakuan suhu 26°C, 28°C dan 30°C, perla-kuan magnesium 0, 10, 20 dan 30 mg L-1. Padat tebar ikan adalah 1 ekor L-1 dengan rata-rata panjang total 2,00±0,03 cm dan bobot rata-rata awal 0,33±0,01 g. Hasil penelitian menunjukkan bahwa laju pertumbuhan benih tengadak ter-baik dicapai pada suhu 28°C dan penambahan magnesium 20 mg L